IMPLEMENTASI MODEL EDUKASI INVESTASI SAHAM SYARIAH DI ERA DIGITAL BAGI MAHASISWA PELAKU UMKM - Puspita, Vina Anggilia; Rinaldo, Dito; Gunardi, Gunardi; Ratna H, Yunyun (Jurnal Pengabdian dan Kewirausahaan, 2023)
Until today, the Indonesian people have had little involvement in the stock market. The main source of the problem is a lack of capital market literacy, which must be addressed by the Indonesia Stock Exchange as a regulator as well as other parties such as academia. Investments in capital market instruments can undoubtedly benefit the community, especially MSMEs players who can distribute some of the revenue generated by the firms they run and then use the returns on these investments for business expansion. Based on these conditions, our service program seeks to improve MSMEs' performance through Sharia-compliant stock investment instruction and mentorship programs. The Community Service Method (PKM) incorporates the Deming Cycle concept, namely plan; do; check; and act, as well as the capital market education model developed by the PKM team. PKM partners are 33 MSME students from Bandung's various educational universities. The PKM results show a significant positive increase in the level of literacy and understanding of Islamic stock investment practices, as evidenced by the results of the different tests where the t-value is greater than the t-table, namely 20.375 > 2.0345, implying that the PKM program was effective. This boost in competence is likely to assist MSME students earn more money to help their businesses grow. This PKM tool also generates capital market investment modules that novice investors can simply understand.